THE PERCEPTUAL MAPPING OF NOTEBOOK BRANDS OF YOUNG PEOPLE IN MANADO - Tampinongkol, Devid Christian; Saerang, David P.E; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Most products and services have many physical and intangible attributes with varied characteristics for a would-be purchaser. For example, toothpaste is not merely "a tooth cleaning product". Rather, for a consumer, it is a bundle of objective and subjective characteristics like taste, mouth freshener, decay protection, bad breath, price, and so on. The marketer's task is the difficult one of deciding how many attributes to build into the product, how much quality to include in each attribute, and how to put the attributes together to gain a competitive advantage. This is notable that key attributes vary by market segment and therefore the marketing effort must change accordingly. This research is designed to have a clearer image and deeper understanding about perceptual maps and the effect of brand attributes to the perception of the customers. The method used in this research is the quantitative research methodology which will provide a deep insight about perceptual maps. In the findings, there is a significant value between the variables of indicators with the brands meaning that they are strongly related.Â Keywords: perceptual mapping, consumer, perception